2018
DOI: 10.1039/c7sm01973d
|View full text |Cite
|
Sign up to set email alerts
|

Synchronous magnetic control of water droplets in bulk ferrofluid

Abstract: We present a microfluidic platform for magnetic manipulation of water droplets immersed in bulk oil-based ferrofluid. Although non-magnetic, the droplets are exclusively controlled by magnetic fields without any pressure-driven flow. The fluids are dispensed in a sub-millimeter Hele-Shaw chamber that includes permalloy tracks on its substrate. An in-plane rotating magnetic field magnetizes the permalloy tracks, producing local magnetic gradients, while an orthogonal magnetic field magnetizes the bulk ferroflui… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 55 publications
(43 reference statements)
0
17
0
Order By: Relevance
“…In addition, the droplets can be readily applied through pipettes or syringes. Their manipulation can be achieved through external or internal forces generated by magnetic fields, electrical fields, or chemical reactions, resulting in motion in both dry and wet conditions and capabilities of reaching narrow space that is inaccessible by conventional robots. By combining state‐of‐the‐art flexible electronics, it is feasible for the droplets to achieve customized functions including, but not limited to, energy harvesting, sensing of physical and chemical parameters, and actuation in a self‐sustainable manner.…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the droplets can be readily applied through pipettes or syringes. Their manipulation can be achieved through external or internal forces generated by magnetic fields, electrical fields, or chemical reactions, resulting in motion in both dry and wet conditions and capabilities of reaching narrow space that is inaccessible by conventional robots. By combining state‐of‐the‐art flexible electronics, it is feasible for the droplets to achieve customized functions including, but not limited to, energy harvesting, sensing of physical and chemical parameters, and actuation in a self‐sustainable manner.…”
Section: Resultsmentioning
confidence: 99%
“…microfluidics also has the capacity to direct droplet transport, mixture, separation, and distribution, and serves as biological or chemical reactor. [150][151][152][153][154] In magnetic digital microfluidic systems, the performance of ferrofluids is mainly reflected in three aspects. The first is magnetic cargo ship: ferrofluid droplets could merge into fixed liquid droplets, load or discharge cargos, and isolate from the droplets.…”
Section: Magnetic Digital Microfluidicsmentioning
confidence: 99%
“…Different from magnetic continuous‐flow microfluidics, magnetic digital microfluidics aims to handle discrete droplets in an individual manner . In addition to controlling the direction, speed, and style of droplet movement, magnetic digital microfluidics also has the capacity to direct droplet transport, mixture, separation, and distribution, and serves as biological or chemical reactor . In magnetic digital microfluidic systems, the performance of ferrofluids is mainly reflected in three aspects.…”
Section: Ferrofluid‐assisted Fluid and Droplet Manipulationmentioning
confidence: 99%
“…The thermal effects on the ferrofluid are captured inside a right angled elbow channel in [17], which concluded that the Nusselt number (ratio of convective to conductive thermal transfer) increases with the increase in the intensity of magnetic field. Katsikis et al [18] addressed a microfluidic platform for magnetic manipulation of water droplets immersed in bulk oil-based ferrofluid. Katsikis et al [18] also drew attention on the future applications due to the potential biocompatibility of the droplets.…”
Section: Introductionmentioning
confidence: 99%
“…Katsikis et al [18] addressed a microfluidic platform for magnetic manipulation of water droplets immersed in bulk oil-based ferrofluid. Katsikis et al [18] also drew attention on the future applications due to the potential biocompatibility of the droplets. The thermal and magnetic effects in T-shaped channel were studied in [19].…”
Section: Introductionmentioning
confidence: 99%